2016
DOI: 10.1152/ajpheart.00911.2015
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the impact of CYP2C19 polymorphisms and low-grade inflammation on coronary microvascular disorder

Abstract: Categorization as a cytochrome P-450 (CYP) 2C19 poor metabolizer (PM) is reported to be an independent risk factor for cardiovascular disease. It is correlated with an increase in the circulating levels of high-sense C-reactive protein (hs-CRP) in women only, although its role in coronary microcirculation is unclear. We examined sex differences in the impact of the CYP2C19 genotype and low-grade inflammation on coronary microvascular disorder (CMVD). We examined CYP2C19 genotypes in patients with CMVD (n ϭ 81)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…In addition, we investigated the possible link between CRP levels and the CYP2C19 phenotype by additional statistical analyses (see Table S2 and Figure S1 in Data S1). Although there was no association between CRP and pharmacogenetic parameters (both CYP2C19 phenotype and class of combined genetic score), the absence of a link cannot be completely ruled out as CRP and IL‐6 levels have been reported to be elevated in poor CYP2C19 metabolizers . These findings suggest that an association between loss‐of‐function SNPs of CYP2C19 and elevated VRC C min could result in reduced VRC metabolism due to diminished CYP2C19 activity (direct effect), as well as an increase in IL‐6 levels, and hence down‐regulation of CYP2C19 and CYP3A4 activities (indirect effect).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, we investigated the possible link between CRP levels and the CYP2C19 phenotype by additional statistical analyses (see Table S2 and Figure S1 in Data S1). Although there was no association between CRP and pharmacogenetic parameters (both CYP2C19 phenotype and class of combined genetic score), the absence of a link cannot be completely ruled out as CRP and IL‐6 levels have been reported to be elevated in poor CYP2C19 metabolizers . These findings suggest that an association between loss‐of‐function SNPs of CYP2C19 and elevated VRC C min could result in reduced VRC metabolism due to diminished CYP2C19 activity (direct effect), as well as an increase in IL‐6 levels, and hence down‐regulation of CYP2C19 and CYP3A4 activities (indirect effect).…”
Section: Discussionmentioning
confidence: 94%
“…We investigated a possible link between CRP levels and pharmacogenetic parameters by comparing CRP levels (considered as continuous variables or CRP classes) according to CYP2C19 phenotype and combined genetic score class. There was no difference in CRP levels depending on either CYP2C19 phenotype or combined genetic score class (Figure S1 and Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microvascular angina has been also associated with CYP2C19 variants that may affect coronary microvascular dysfunction [64]. Moreover, recent data in the female population showed that the specific CYP2C19 poor metabolizer genotype can lead to coronary microvascular disorders via inflammation [65].…”
Section: Coronary Microvascular Diseasementioning
confidence: 99%
“…Moreover, the specific CYP2C19 poor metabolizer has been described as a risk factor for coronary microvascular disorders via inflammation exclusively in the female population [65]. Usually, in fertile female exhibits a protection in ischemic injury compared to age-related men, a phenomenon designated as sex-specific cardioprotection.…”
Section: Sex Differencesmentioning
confidence: 99%